Leadership and Knowledge Sharing: Key Factors in Enhancing School Learning Outcomes - Marjani, Marjani; Madjiani Tahir, An-Najjar (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2024)
This study examines the role of school principals and knowledge-sharing practices in enhancing the quality of learning within schools. The research aims to analyze the role of principals in executing leadership functions, overseeing, and motivating teachers and educational staff to improve the quality of learning as expected by the school. Additionally, the study investigates knowledge-sharing practices between principals and teachers, as well as among teachers. The knowledge shared by principals, teachers, and educational staff is expected to help address challenges in improving learning quality. The research employs a content analysis approach, which involves identifying, categorizing, and interpreting meanings from various written sources such as scholarly journals, books, news articles, and official documents. Literature searches were conducted using leading academic databases like Google Scholar. The findings indicate that the role of school principals and knowledge-sharing practices, both between principals and teachers and among teachers and staff, contribute to the improvement of learning quality. This study highlights the need for leadership training for principals to develop skills in designing and managing effective knowledge-sharing programs.